Lack of family education in boarding primary schools in China's minority areas: A case study of Stone Moon Primary School, Nujiang Lisu Autonomous Prefecture - Guo, Guo; Chen, Yao (Frontiers in Psychology, 2023)
The lack of family education in boarding primary schools in ethnic minority areas negatively impacts students' physical and mental health. This study constructed an analytical framework for the lack of family education in boarding primary schools from the perspective of Overlapping Spheres of Influence theory. Stone Moon Primary School of Lisu in Nujiang Prefecture was used as the field site for questionnaire survey. The correlation analysis showed that “teachers' avoidance of educational risks”, “the priority in the schooling system of classic hard skills over soft skills” and “the capacity limit of policies and regulations” had significant positive correlation with the degree of “the lack of family education”. In the regression analysis, the adjusted R2 was 0.607, indicating that the proportion of “lack of family education” explained by the three factors of “teachers' avoidance of educational risks”, “the priority in the schooling system of classic hard skills over soft skills” and “the capacity limit of policies and regulations” was 60.7% through the regression relationship. Possible solutions include establishing a responsibility standard system and accountability system between teachers and parents, and strengthening the compensation management of family education function in boarding primary schools in ethnic minority areas.